Pengaruh Frekuensi Penggorengan dan Penambahan Sari Mengkudu (Morindacitrifolia) terhadap Jumlah Asam Lemak Trans pada Minyak Jelantah - Rahmiati, Baiq Fitria; Jauhari, M. Thonthowi; Ardian, Junendri; Aini, Quratu (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2020)
The development of various degenerative diseases is very rapid. Degenerative disease is a medical term to describe a disease that arises as a result of the deterioration of the function of the body's cells from a normal state that becomes worse or the level of cell activity in the body decreases.Degenerative disease was caused by over consuming high trans fatty acid that exist in fried foods with reused cooking oil. The cooking oil that used to fry food repeatedly contained high trans fatty acid. Noni fruits contained antioxidant which can prevent formation of trans fatty acid by obstructing oxidation reaction. . The objective of this research was to determine the effect of fried frequency and noni juice addition in the amount of trans fatty acid optimally. This research used Randomized Experimental Design Split Plot 4x5x2. Treatments applied were addition of noni juice in various volume (0 ml, 45 ml, 50 ml, 55 ml), and frying frequency of cooking oil (G1, G2, G3, G4, G5). The result of this research were frying frequency affect the increase of trans fatty acid (p=0.000) and the addition of noni juice affect the decrease of trans fatty acid (p=0.005) but interaction between frying frequency and addition of noni juice did not affect the amount of trans fatty acids (p=0.71). Volume of noni juice which can reduced trans fatty acid optimally is 55 ml of noni juice in second frying. In conclusion, the amount of trans fatty acid affected by frying frequency and addition of noni juice.